A Guide for the Design of Functional Polyaromatic Organophosphorus Materials. Issue 56 (7th August 2017) - Hindenberg, Philip; López‐Andarias, Alicia; Rominger, Frank; de Cózar, Abel; Romero‐Nieto, Carlos
Abstract: Invited for the cover of this issue are groups of Abel de Cózar from the University of País Vasco, and Carlos Romero‐Nieto from the Ruprecht‐Karls‐University in Heidelberg. The image depicts the many different properties that can be achieved with different fused phosphorus heterocycles. Read the full text of the article at 10.1002/chem.201701649 . Abstract : " We reveal the key synthetic aspects to accessing novel poly(hetero)aromatic architectures ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13919 ff. (DOI:10.1002/chem.201701649 ).